Demystifying viruses: understanding the role of river viruses on microbial community structure and biogeochemical cycling through a multi-omic lens - Rodríguez-Ramos, Josué, author; Wrighton, Kelly, advisor; Hall, Edward, committee member; Metcalf, Jessica, committee member; Wilkins, Michael J., committee member (Colorado State University. Libraries, 2023)
Viruses are the most abundant entity on the planet, with estimates of up to 1031 viral particles dispersed across the globe in every ecosystem that can sustain life. Today, as the world responds to the COVID-19 pandemic, the word "virus" often evokes a negative response because of their impacts on human health and disease. Yet, most viruses that exist in the world can only infect bacteria and archaea. In fact, it has long been estimated that for every 1 bacterial or archaeal cell, there are 10 viruses that can infect it. While bacteria and archaea are long regarded as essential to overall ecosystem health and functionality, the roles of viruses in natural systems are much less understood and appreciated. Due to a scarcity of genome-resolved multi-omic studies, this lack of understanding is compounded in river ecosystems, which play critical roles modulating global carbon and nitrogen biogeochemistry. The overarching aims of this dissertation are to harness genome-resolved, multi-omic datasets to 1) decipher the impact that viruses can have on river microbial communities and biogeochemical cycling, and 2) to explain how viral ecology can enhance our understanding of river ecosystem function. To define the role that viral and microbial communities have on river function, I first set out to understand what is currently known of river viral ecology. In Chapter 1, I provided a background primer on viruses and their impacts on natural ecosystems. I then zoomed in on viral roles exclusively within rivers and described the current state of river viral ecology. I also highlighted some of the knowledge gaps addressed specifically by my thesis. My literature review revealed that while there are publicly available metagenomic datasets, there is a drastic underutilization of genome-resolved strategies which are critical for constraining microbial metabolism and viral impacts into informative units. Further, these datasets are largely unused because the data is collected in an un-coordinated manner, leading to the lack of similar sampling methods, and ultimately an inability to make results interoperable. Together, in this chapter I present compelling evidence for the need of genome-resolved, virus-host paired multi-omic analyses that are pivotal to our understanding of river ecosystems and lay the groundwork for the questions I will address throughout my dissertation. After identifying that there was a gap studies that leverage metagenome assembled genomes (MAGs) and viral metagenome assembled genomes (vMAGs), for Chapter 2 I focused on using a genome-resolved lens to uncover the microbial and viral metabolic underpinnings responsible for the biogeochemical cycling of carbon and nitrogen in the Columbia River system. This chapter used a dataset that was spatially resolved at the centimeter scale for three sediment cores across two transects of the Columbia River and included 33 samples, all of which had metagenomes that were paired to metaproteomes, biogeochemistry, and metabolites. Using this dataset, I created the first river microbial and viral database genome-resolved database called Hyporheic Uncultured MAG and vMAG (HUM-V). Leveraging metaproteomics paired to HUM-V database, I built a conceptual model outlining microbial and viral contributions to carbon and nitrogen biogeochemistry in these river sediments. With this metabolic reconstruction, I showed an intertwined carbon and nitrogen cycle that can likely contribute to the fluxes of nitrous oxide. Specifically, I demonstrated that well recognized river microbes like those of the phyla Nitrososphaeraceae as well as other less recognized phyla like Binatia encode and express genes for denitrification. I also showed that the clade II nosZ gene, which is responsible for nitrous oxide production, could possibly act as a nitrous oxide sink without contributing to its production. Linking viral members to microbial hosts demonstrated that viruses may be key modulators of carbon and nitrogen cycling. Specifically, I presented evidence that viruses can infect key nitrifying organisms (i.e., Nitrospiraceae) as well as key polymer degrading organisms (i.e., Actinobacteria). Highlighting their potential roles, linear regression analyses consistently identified viral organisms as key predictors of ecosystem biogeochemistry. Chapter 2 of my thesis yielded insights that uncovered some of the microbial contributions that were thought to occur but were poorly defined in river sediments (e.g., nitrogen mineralization), and presented a genome-resolved, virus-host paired strategy that I could then use to directly assess how viruses impacted host metabolism and ecosystem function. Ultimately, Chapter 2 highlights the power of genome-resolved database strategies to reduce existing predictive uncertainties in river corridor models. Having provided a genome-resolved view of metabolic processes in Chapter 2, for Chapter 3 I set out to expand upon our understanding of river viruses by providing insights into their temporal and spatial dynamics. For this, I worked with a finely tuned temporal dataset from an urban stream near Berlin, Germany called the Erpe River. The Erpe River dataset is a metagenomic timeseries where samples were collected every 3 hours for a total of 48 hours across both the surface water (SW) and pore water (PW) compartments. In addition to metagenomes, Fourier-transform ion cyclotron resonance mass spectrometry (FTICR-MS) and biogeochemistry were collected for each sample. Using this dataset, I created a database consisting of 1,230 vMAGs and 125 MAGs. Only 1% of our vMAGs clustered to known taxonomic representatives, highlighting the underrepresentation of river viruses in public databases. Due to this underrepresentation, I supplemented my viral taxonomic analyses with over 20,000 vMAGs spanning different publicly available studies that were relevant to rivers and wastewater treatment plants and showed that nearly half of the novel genera identified were cosmopolitan in aquatic ecosystems. I also characterized the spatial and temporal dynamics of the river microbiomes across the surface water (SW) and pore water (PW) compartments. Both the viral and microbial communities were distinct between the SW and PW samples and were both driven by the same chemical drivers. Given that these compartments had distinct communities, I set out to understand how they were changing over time. By employing multiple temporal statistical methods, I show that SW communities are more persistent and more stable relative to the PW communities, likely resulting from the homogeneous selection pressures of the SW, and the heterogeneity within the sediment. In addition to resolving these temporal dynamics, I highlight some specific virus and host genomes that influence biogeochemical cycling. In summary, my third chapter shows how river viral and microbial communities change across spatial and temporal gradients, and highlights how genome-resolved metagenomics enhances our interpretation of microbiome data. The final chapter of this dissertation (Chapter 4) summarizes the key findings of my thesis and provides future perspectives to inspire research in environmental river viral ecology. This section also showcases several publications that I have worked on throughout my doctoral degree that span multiple ecosystems like mouse guts, human guts, soils, and the development of the computational tool Distilled and Refined Annotation of Metabolism (DRAM). This final chapter also highlights a manuscript that I was involved in that showcases a new scientific framework: Interoperable, Open, Coordinated, and Networked (ICON). I further highlight this framework to address how these ICON strategies are beginning to be implemented in other fields and propose that in order to move the discipline of river microbial ecology forward, we need to implement ICON frameworks and the standardization and coordination of sampling collection. In summary, the aims of this dissertation were to summarize what is known in the field of river viral ecology (Chapter 1), to investigate viral roles that viruses play on river organic nitrogen and carbon processing (Chapter 2), to interrogate the temporal and spatial dynamics of viruses within rivers (Chapter 3), and to summarize how this dissertation has added to the understanding of river viral ecology, and what the next big questions for the field should be (Chapter 4). Ultimately, these works shine a spotlight on the viruses found in river ecosystems and shows that they likely play key roles in the regulation of microbial biogeochemical cycles.
Zip file contains appendices A, B, and C.
Keywords: metaproteomics; multi-omics; viral ecology; microbial ecology; metagenomics; river microbiology